Perceptions of Intimate Student–Professor Relationships - Gregoire, Nina; Kaseweter, Kimberley; Klukas, Ethan; Davies, Paul (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2026)
Previous research indicates that university students generally disapprove of intimate student–professor relationships (ISPRs), largely due to power imbalances. Further, students may lose faith in their academic abilities and abandon their studies following sexual overture from a professor. The present research used two studies to explore undergraduate student perceptions of ISPRs. Study 1 employed a 2 (Gender of the Initiator: Male or Female) by 2 (Status of the Initiator: Professor or Student) between-groups vignette design. Study 2 employed the same design as Study 1, adding a third variable—the quality of a reference letter (Overly Positive or Negative) provided by the professor for the student in the relationship. Both studies included sexism as a covariate. Participants were asked to rate four dependent variables: the degree of sexual harassment, power imbalance, impacts on others, and the appropriateness of consequences. In Study 1, participants in the Professor as Initiator conditions rated sexual harassment, power imbalance, and impacts to others more severely, regardless of gender. In Study 2, participants in the Overly Positive Letter conditions rated the power imbalance more severely, regardless of gender or status. Adding the reference letter component in Study 2 resulted in participants rating all four dependent variables more severely than those in Study 1, as predicted.